Hematopoietic progenitor cells transplantation for recurrent or refractory Hodgkin's lymphoma. (September 2013) - Moscato, Tiziana; Fedele, Roberta; Messina, Giuseppe; Irrera, Giuseppe; Console, Giuseppe; Martino, Massimo
<x xml:space="preserve">Abstract</x> Introduction: Advanced-stage Hodgkin's lymphoma (HL) has become a curable disease in the majority of patients. Despite this, about 20% of these patients relapsed or are primary refractory to the first-line treatment and high-dose chemotherapy (HDC) and autologous (Auto) hematopoietic progenitor cells transplantation (HPCT) are considered a therapeutic option. Areas covered: The authors reviewed HDC and HPCT treatment strategies in recurrent or refractory HL patients, with the goal of providing an overview of this approach. Expert opinion: Patients younger than 60 – 65 years with relapsed disease or refractory to first-line therapy should receive a second-line chemotherapy, followed by HDC and Auto-HPCT. Progression-free and overall survival results are significantly better when a second remission or a minimal disease status is achieved before Auto-HPCT, and demonstrate that this strategy is able to cure more than half of the advanced HL patients. Myeloablative allogeneic HPCT (Allo-HPCT) has been employed in advanced phases of the disease, but there have been significant concerns due to treatment-related mortality (TRM). The safety of allogeneic transplantation has improved with the use of reduced-intensity allogeneic (RIC-Allo) HPCT strategies. Despite early favorable results, mature results of RIC-Allo available in the literature are consistent in demonstrating a lack of long-term disease control.